Analisis Implementasi Sistem E-procurement Dalam Pendeteksian Dan Pencegahan Fraud Di PT. Pertamina RU VII Kasim Sorong - BANEA, AGNES EYNE; SAERANG, DAVID P.E; WARONGAN, JESSY D.L (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2020)
Abstract. This study is intended to analyse the implementation of the e-procurement system in detecting and preventing frauds, including to analyse the constraints of such system at PT. Pertamina RU VII Kasim Sorong. This is a qualitative research study and conducted by exploratory approach. Data were obtained by field observations, interviews with key informants and documentation studies. Key informants were interviewed with specific considerations and objectives. Triangulation technique was used to examine the validity of data and data sources. Interviews were transcribed into transcirptions. Those transcriptions were analysed by content analysis, consisting of giving a theme / coding, conceptualizing scientific statement and interpreting in the form of narration. The results showed that the e-procurement system at PT. Pertamina RU VII. Kasim has been implemented in accordance with the Minister of BUMN Regulation No.PER-15/MBU/2012 concerning the procurement of goods and services electronically. It therefore allows the detection and prevention of frauds which are committed by third parties/vendors against PT. Pertamina RU VII Kasim Sorong. However, regarding the implementation of the e-procurement system, several obstraints are still found, namely in human resources and network or application systems.Keywords: E-Procurement System, FraudAbstrak. Penelitian ini bertujuan menganalisa bagaimana implementasi system e-procurement dalam pendeteksian dan pencegahan fraud, serta menganalisa kendala yang terjadi dalam penerapan sistem e-procurement di PT. Pertamina RU VII Kasim Sorong. Metode penelitian yang digunakan adalah metode penelitian kualitatif dengan pendekatan eksploratori. Data diperoleh melalui observasi lapangan, wawancara pada informan kunci dan studi dokumentasi. Informan kunci yang diwawancarai dengan pertimbangan dan tujuan tertentu. Teknik triangulasi digunakan untuk menguji validitas data dan sumber data. Data transkrip yang diuraikan dari hasil wawancara dianalisis menggunakan metode analisis isi yang terdiri dari pemberian tema/coding, konseptualisasi pernyataan ilmiah dan menginterprestasikan dalam bentuk narasi.Hasil penelitian menunjukkan bahwa implementasi sistem e-procurement pada PT. Pertamina RU VII Kasim sudah sesuai dengan peraturan menteri BUMN Nomor PER-15/MBU/2012 tentang pengadaan barang dan jasa secara elektronik. Sehingga dapat mendeteksi dan mencegah fraud yang dilakukan oleh pihak ketiga/vendor terhadapÂ  PT Pertamina RU VII Kasim Sorong. Namun tentang penerapan sistem e-procurement masih ditemukan beberapa kendala yaitu Sumber Daya Manusia (SDM) dan sistem jaringan atau aplikasi. Kata Kunci: Sistem E-Procurement, FraudÂ